2006
DOI: 10.1152/ajpendo.00194.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose transporters by insulin and extracellular glucose in C2C12myotubes

Abstract: Nedachi, Taku, and Makoto Kanzaki. Regulation of glucose transporters by insulin and extracellular glucose in C2C12 myotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 64 publications
9
90
0
Order By: Relevance
“…We quantified differentiation status by counting the number of myotubes defined as multinuclear myotubes that contained more than 5 nuclei (Fig. 1B), as we previously reported (37). The effect of the extracellular glucose concentration on myogenesis was confirmed by Western blot analysis of differentiation marker proteins using anti-skeletal muscle type MHC and anti-myogenin antibodies, as not only were their expressions detected later, but their amounts were also lower than in C 2 C 12 cells differentiated under LG conditions (Fig.…”
Section: Extracellular Glucose Influences Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…We quantified differentiation status by counting the number of myotubes defined as multinuclear myotubes that contained more than 5 nuclei (Fig. 1B), as we previously reported (37). The effect of the extracellular glucose concentration on myogenesis was confirmed by Western blot analysis of differentiation marker proteins using anti-skeletal muscle type MHC and anti-myogenin antibodies, as not only were their expressions detected later, but their amounts were also lower than in C 2 C 12 cells differentiated under LG conditions (Fig.…”
Section: Extracellular Glucose Influences Lowmentioning
confidence: 99%
“…However, despite our general understanding of the effects of ambient glucose levels on insulin responsiveness with regard to metabolic actions in skeletal muscle cells (37), the possible interrelationship between glucose and insulin acting on myogenesis remains to be clarified.…”
mentioning
confidence: 99%
“…Other studies have shown GLUT4 enhancement under different concentrations of cinnamon extract or dihydrocinnamic acid (DHH105), a derivative of cinnamon, on GLUT4 content in animal adipose tissue [17] or 3T3-L1 cell line, a good model for studding fat tissue metabolism [14]. But muscular tissue is the most important site for glucose metabolism which uses more than 75 % of body glucose expenditure under insulin impact [18][19][20][21]. As the rate limiting step of blood glucose level expenditure is regulated by GLUT4 glycoprotein presence in the cytoplasmic membrane [22,23], the objective of current study was to investigate the effect of cinnamon water extract on GLUT4 contents of cytoplasmic membrane (CM) and nuclear/endoplasmic (N/ER) reticulum fractions of differentiated C2C12 myotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to develop efficient in vitro model systems for in-depth studies on the glucose uptake involving GLUT4 in muscle cells. However, such systems have been still awaited, since most of the established skeletal muscle cell lines reportedly show minimal insulin-dependent glucose uptake and translocation of GLUT4, and only the exceptions are rat L6 and mouse C2C12 myotubes (Nedachi and Kanzaki 2006). When stimulated by insulin, L6 myotubes appeared to exhibit glucose uptake to a larger extent than C2C12 cells (Sarabia et al 1990), suggesting that at present L6 myotubes could be the most promising candidate as an efficient in vitro model system to investigate glucose uptake in muscle cells.…”
Section: Introductionmentioning
confidence: 99%